2015
DOI: 10.1159/000442605
|View full text |Cite
|
Sign up to set email alerts
|

Brain Diffusion Changes in Emerging Psychosis and the Impact of State-Dependent Psychopathology

Abstract: Background/Aims: Previous diffusion tensor imaging (DTI) studies have shown microstructural changes in the brain white matter of at-risk mental state (ARMS) subjects for psychosis and patients with first-episode psychosis (FEP). However, only a few studies have been conducted in clinical high-risk samples and findings in both groups are inconsistent, in particular along the superior longitudinal fasciculus (SLF). Methods: This DTI study used tract-based spatial statistics (TBSS) to compare fractional anisotrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 48 publications
2
28
1
Order By: Relevance
“…One possible explanation of these findings is that the association is not present in the early stages of the disease. This is also reflected by the fact that white matter volume alterations are known to be present in schizophrenia and bipolar disorder patients and also the first-episode state [11,13,[38][39][40] and less pronounced in ARMS [41]. Therefore, it might be speculated that white matter volume alterations occur only later in the development of the disorder, and are not detectable in this pooled patient cohort.…”
Section: Discussionmentioning
confidence: 89%
“…One possible explanation of these findings is that the association is not present in the early stages of the disease. This is also reflected by the fact that white matter volume alterations are known to be present in schizophrenia and bipolar disorder patients and also the first-episode state [11,13,[38][39][40] and less pronounced in ARMS [41]. Therefore, it might be speculated that white matter volume alterations occur only later in the development of the disorder, and are not detectable in this pooled patient cohort.…”
Section: Discussionmentioning
confidence: 89%
“…DTI studies of ARMS subjects have found reduced FA in frontal regions, the anterior limb of the internal capsule, the posterior cingulate and the angular gyrus (Hoptman et al 2008; Karlsgodt et al 2009; Peters et al 2009; von Hohenberg et al 2014). Increased FA has also been reported in the ACC and the right middle and superior frontal gyri (Hoptman et al 2008) as well as in the superior longitudinal fasciculus (Schmidt et al 2015). Although these inconsistent findings may reflect true heterogeneity in ARMS patients, they may also be attributed to the small sample sizes used in the aforementioned studies.…”
Section: Introductionmentioning
confidence: 88%
“…Unfortunately, there are few and inconsistent findings regarding diffusivity indices as a complement to FA [ 66 , 73 , 74 ]. Similarly, few studies have investigated the association of white matter changes in CHR with later transition to psychosis, and their findings are heterogeneous.…”
Section: Structural Neuroimagingmentioning
confidence: 99%